2023
DOI: 10.3389/fonc.2023.1168143
|View full text |Cite
|
Sign up to set email alerts
|

Paralog-based synthetic lethality: rationales and applications

Abstract: Tumor cells can result from gene mutations and over-expression. Synthetic lethality (SL) offers a desirable setting where cancer cells bearing one mutated gene of an SL gene pair can be specifically targeted by disrupting the function of the other genes, while leaving wide-type normal cells unharmed. Paralogs, a set of homologous genes that have diverged from each other as a consequence of gene duplication, make the concept of SL feasible as the loss of one gene does not affect the cell’s survival. Furthermore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 130 publications
(219 reference statements)
0
3
0
Order By: Relevance
“…The presence of numerous paralogs in candidate SL genes also demands careful consideration due to potential functional redundancy hindering effective synthetic lethality. Interestingly, gene pairs that are paralogs have been found to engage in SL relationships more often than by chance ( 87 ). The prioritization of VIH–SL pairs can consider these aspects, with final candidates selected for their druggability and the availability of existing drugs or ligands (Table 6 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of numerous paralogs in candidate SL genes also demands careful consideration due to potential functional redundancy hindering effective synthetic lethality. Interestingly, gene pairs that are paralogs have been found to engage in SL relationships more often than by chance ( 87 ). The prioritization of VIH–SL pairs can consider these aspects, with final candidates selected for their druggability and the availability of existing drugs or ligands (Table 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…Both VPS25 and CHMP2A represent candidate pan-viral SL targets involved in multivesicular body assembly, which is directed by the ESCRT complex and has been shown to be involved in the early viral life cycle of multiple viruses ( 96–98 ). Furthermore, CHMP2A interacts with SARS-CoV-2 Orf9b and has been shown to contribute to the budding of a variety of viruses including HIV ( 87 ), equine infectious anemia virus ( 99 ), and murine leukemia virus ( 88 ), suggesting a critical role for virus release and thus a potential role as a pan-viral SL target. While these three candidate SL targets could be promising, none are listed as drug targets in DrugBank.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that DDX3Y, a male-specific paralog that shares 90% sequence similarity with DDX3X (82), is stabilized in parallel with DDX3X in both TSAR and LiP-MS, a finding afforded by our use of male-derived cell lysate. The apparent unity between DDX3X and DDX3Y targeting, at least among our compound panel, urges thorough structural evaluation for groups embarking on paralog-specific rocaglate discovery (83).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, paralogs, which arise from duplicated sequences of a shared ancestor and often perform similar functions, exhibit functional redundancy. Their loss is more common in tumors [51] , making them potential precision targets for cancer treatment and an essential dataset for SL discovery [52] , [53] . Mutually exclusive mutation patterns suggest incompatible driver mutations in tumorigenesis, indicating a potential source of SL interactions [54] .…”
Section: Discussionmentioning
confidence: 99%